Pushing the Envelope in Endoscopic Submucosal Dissection: Is It Feasible and Safe in Scarred Lesions?. Issue 3 (7th December 2020) - Nugent, Emmeline; Sapci, Ipek; Steele, Scott R.; Liska, David; Hull, Tracy L.; Gorgun, Emre
Abstract : BACKGROUND: Endoscopic submucosal dissection is an established advanced polypectomy technique to manage large colorectal polyps. OBJECTIVE: The purpose of this study was to evaluate patients who had endoscopic submucosal dissection in the setting of significant scarring attributed to a previous intervention to determine whether this is safe and feasible. DESIGN: The study used a prospectively maintained database. SETTINGS: A scarred lesion was defined as a nonlifting polyp with a history of previous attempted removal with endoscopic mucosal resection, snare, or biopsy where there was no suspicion of malignancy. PATIENTS: All consecutive patients in the previous 14 months were included. INTERVENTION: Endoscopic submucosal dissection was the study intervention. MAIN OUTCOME MEASURES: Thirty-day morbidity and mortality, readmission, length of stay, and recurrence were measured. RESULTS: Ninety-one patients had endoscopic submucosal dissection over a 14-month period with a median polyp size of 31.5 mm (range, 20–45 mm). Eleven patients (12%) were confirmed as having significant scar. There were significantly more previous endoscopic mucosal resections in the scarred group (scarred: 63.6% vs nonscarred: 2.5%; p < 0.001). Significantly more of the scarred patients had their endoscopic submucosal dissection in the operating room versus the endoscopy suite (scarred: 82.0% vs nonscarred: 17.5%; p < 0.001). The 30-day morbidity rate was 18.7%. There were no mortalities. There was no difference in 30-day morbidity between scarred and nonscarred lesions (scarred: 9% vs nonscarred: 20%; p = 0.4). There were more day-case procedures in the nonscarred group (nonscarred: 93.7% vs scarred: 36.4%; p < 0.001). There was no malignancy on final pathology in the scarred group. There was no difference in readmission rate between the scarred and nonscarred lesions. The overall follow-up colonoscopy rate was 53%, and there were no polyp recurrences identified. LIMITATIONS: The study was limited by its small sample size, single institute, surgeon experience, and short follow-up. CONCLUSIONS: Not only is endoscopic submucosal dissection in patients who have scarred lesions technically feasible and safe, it avoids a bowel resection in the majority of patients who have exhausted other advanced endoscopy techniques. See Video Abstract at http://links.lww.com/DCR/B427 . EMPUJAR EL SOBRE EN LA DISECCIÓN ENDOSCÓPICA SUBMUCOSA: ¿ES FACTIBLE Y SEGURO EN LESIONES CICATRIZADAS?: ANTECEDENTES: La disección endoscópica submucosa es una técnica de polipectomía avanzada establecida para tratar pólipos colorrectales grandes. OBJETIVO: Evaluar a pacientes que se sometieron a disección submucosa endoscópica en el contexto de cicatrices significativas debido a una intervención previa para determinar si esto es seguro y factible. DISEÑO: Base de datos mantenida prospectivamente. AJUSTE: Una lesión cicatrizada se definió como un pólipo que no se levanta con antecedentes de intento de extirpación previa con resección endoscópica de la mucosa, lazo o biopsia, donde no había sospecha de malignidad. PACIENTES: Todos los pacientes consecutivos en los últimos 14 meses. INTERVENCIÓN: Disección submucosa endoscópica. MEDIDAS DE RESULTADOS PRINCIPALES: Morbilidad y mortalidad a 30 días, reingreso, duración de la estadía, recurrencia. RESULTADOS: Noventa y un pacientes tuvieron disección submucosa endoscópica durante un período de 14 meses con tamaño de pólipo mediana de 31, 5 mm (rango, 20 - 45 mm). Se confirmó que once pacientes (12%) tenían una cicatriz significativa. Hubo significativamente más resecciones de mucosa endoscópica previas en el grupo con cicatrices (con cicatrices: 63, 6% vs. sin cicatrices: 2, 5%, p <0, 001). Significativamente más de los pacientes con cicatrices tuvieron su disección submucosa endoscópica en el quirófano en comparación con la sala de endoscopia (con cicatrices: 82% vs. sin cicatrices: 17.5%, p <0.001). La tasa de morbilidad a 30 días fue del 18, 7%. No hubo muertes. No hubo diferencia en la morbilidad a 30 días entre las lesiones cicatrizadas y no cicatrizadas (cicatrizadas: 9% frente a no cicatrizadas: 20%, p = 0, 4). Hubo más procedimientos ambulatorios en el grupo sin cicatrices (sin cicatrices: 93, 7% frente a cicatrices: 36, 36%, p <0, 001). No hubo malignidad en la patología final en el grupo con cicatrices. No hubo diferencia en la tasa de reingreso entre las lesiones cicatrizadas y no cicatrizadas. La tasa general de colonoscopia de seguimiento fue del 53% y no se identificaron recurrencias de pólipos. LIMITACIONES: Tamaño de muestra pequeño, experiencia de un solo instituto y cirujanos y seguimiento corto. CONCLUSIÓN: La disección endoscópica submucosa en pacientes con lesiones cicatrizadas no solo es técnicamente factible y segura, sino que evita una resección intestinal en la mayoría de los pacientes que han agotado otras técnicas endoscópicas avanzadas. Consulte Video Resumen en http://links.lww.com/DCR/B427 .